Elaboration d’une pommade anti inflammatoire naturelle à base de mucilage de Lepidium sativum - MAIZA, CHAIMAE (My University, 2022)
The main objective of our work is to formulate a natural anti-inflammatory ointment from the mucilage of Lepidium sativum. We started by extracting the mucilage from the seeds of L. sativum, then the natural ointment was composed by adding an excipient. Then the physico-chemical characteristics of the ointment were determined. This characterization was based on three parameters: pH acidity test, skin to lerability teston rabbitsand the sterility test.The result sobtained show that the formulated ointmenthas good physico-chemical properties. The skin tolerance test on rabbits showed no signs of allergy orirritation ,sowe note datolerance of 100%. The bacterial study shows that the ointmentis sterile and does not contain any pathogenic germs.
Keywords: Lepidiumsativum; seeds; mucilage; extraction; skin tolerance